Komunikasi Krisis dalam Kampanye Politik: Studi Kasus Respons Kandidat Terhadap Isu Negatif - Asep Gumilar Hidayat; Bambang Kurniadi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
In political campaigns, crisis communication plays a crucial role in shaping a candidate’s image when facing negative issues. Candidates often encounter political attacks that can damage their reputation and affect electability. This study aims to analyze crisis communication strategies used by candidates in responding to negative issues during campaigns. Using a qualitative approach, this research examines various communication techniques applied to manage public perception and mitigate the negative impact of emerging issues.The findings indicate that effective crisis communication strategies involve transparency, message consistency, and the use of social media as a clarification tool. Candidates who can control the narrative and respond quickly tend to maintain voter support better than those who avoid or provide defensive responses. This study concludes that proper crisis communication can serve as a strategic tool in maintaining a candidate’s credibility and gaining public trust.